Perubahan penduduk Wilayah Metropolitan Lanjutan Klang-Langat, Malaysia, 1957-2000 - Katiman Rostam (Universiti Kebangsaan Malaysia, 2010)
Population of the Klang-Langat Extended Metropolitan Region (EMR) is changing very rapidly. The dynamics of the EMR population may be explained in several ways including its pattern of distribution, ethnic composition, rate of growth and levels of urbanisation of settlements in the peri-urban areas. This article aims at analysing patterns of population change in terms of distribution and ethnic composition. Elements of natural growth rates, migration and levels of urbanisation of the EMR will be discussed to explain the change. Data from various reports, particularly the census of housing and population of Malaysia for 1957-2000 period, were analysed. Results of the analysis show that the population of the EMR is experiencing a very rapid change in terms of distribution, ethnic compositions, rates of growth and urbanisation. Although the core area of the region is still the most densely populated, there are many evidences to support that the fringe areas of the EMR is experiencing rapid rate growth resulting from natural increase as well as in-migration of people either from the core area or outside the region. After 1990s the Malays are the majority of population of the EMR followed by the Chinese and Indians. High rates of natural increase and in-migration among the Malays to the EMR particularly the fringe areas, have contributed significantly to the process of urbanisation and rapid growth of small urban centres in the outer zones of the region. It is also found that the rate of growth of population in the core area of the EMR is on the downwards trend. In contrast the rate of growth of population in the fringe areas of the region is steadily increasing. The findings tend to support the view that expansion of an EMR occurs via the process of urbanisation of people living in the fringe zones driven by the development of manufacturing and service activities in the area. Such a pattern of change will certainly have some bearings on the future social, economic, cultural and political milieus of the EMR.